Geo-Spatial Cluster Tuberculosis of 2021-2023: Study in A District, Indonesia - Cahyaningrum, Alfiana Sahrina; Setiyadi, Noor Alis (Indonesian Journal of Global Health Research, 2024)
Tuberculosis is an infectious disease that affects the respiratory organs and is still a health problem in Indonesia. The incidence of tuberculosis in Indonesia ranks second after India. Spatial analysis of tuberculosis has been conducted in Indonesia, but there has been no research on cluster distribution patterns in Sukoharjo District, Indonesia. Objective: This research aims to identify tuberculosis spatial clusters in Sukoharjo Regency in 2021-2023. Method: This research data was obtained from the Integrated Tuberculosis Information System of the Sukoharjo Regency Health Service for 2021-2023. Population and population density data were obtained from the Central Statistics Agency (BPS) of Sukoharjo Regency Data were analyzed using Poisson spatial scanning using the SaTScanTM v.10.0.1 application and area mapping using QGIS 3.34. Results: Based on the spatial scanning analysis that has been carried out, there is a cluster grouping of population and population density of tuberculosis cases in Sukoharjo Regency. In the 2021-20233 population cluster, there is 1 cluster grouping of 978 cases with a radius of 9,39 km. Meanwhile, in the 2021-2023 population density cluster, there are 7 cluster groupings, but there is a cluster with the largest radius 16,8 km with 1152 cases. Conclusions: This results of this research are expected to assist health authorities in increasing efforts to control and prevent tuberculosis cases by focusing in areas with high risk population.